2020
DOI: 10.3201/eid2605.191224
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Hospitalization Costs, United States, 2017

Abstract: The United States is in the midst of unprecedented person-to-person hepatitis A outbreaks. By using Healthcare Cost and Utilization Project data, we estimated the average costs per hepatitis A-related hospitalization in 2017. These estimates can guide investment in outbreak prevention efforts to stop the spread of this vaccine-preventable disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
0
12
2
Order By: Relevance
“…18 The average cost of a hepatitis A-related hospitalization in 2016 was $16 610, and recent hepatitis A virus outbreaks alone have cost the nation at least $270 million since 2016. 19 In 2019, HIV care and treatment cost the US government more than $20 billion. 20 The cost for treating HIV infections related to the Scott County outbreak is projected to be more than $100 million.…”
Section: Making the Case For Syringe Services Programsmentioning
confidence: 99%
“…18 The average cost of a hepatitis A-related hospitalization in 2016 was $16 610, and recent hepatitis A virus outbreaks alone have cost the nation at least $270 million since 2016. 19 In 2019, HIV care and treatment cost the US government more than $20 billion. 20 The cost for treating HIV infections related to the Scott County outbreak is projected to be more than $100 million.…”
Section: Making the Case For Syringe Services Programsmentioning
confidence: 99%
“…In this study, the average costs of a HAV infection-related hospitalization were $246, while in the United States, in 2017, the average costs were $16,232 (21). Cost-effective analyses performed in Ireland also showed that where HAV immunity is 45% or less, vaccination is the strategy of choice without a prior screening (22).…”
Section: Discussionmentioning
confidence: 64%
“…We adopted a limited societal perspective in estimating costs, which incorporated the direct medical costs and nonmedical costs (i.e., public health costs and productivity loss due to illness). The direct medical costs included outpatient and inpatient costs of clinical management of HAV infection, vaccine and vaccine administration costs, and the cost of postvaccination serologic testing for HAV immunity [6][7][8][9][10][11]. We included the full cost of the 3-dose hepatitis A and hepatitis B combination vaccine and the 2-dose hepatitis A single-antigen vaccine.…”
Section: Methodsmentioning
confidence: 99%